2018
DOI: 10.7759/cureus.2215
|View full text |Cite
|
Sign up to set email alerts
|

Management of Primary Mediastinal B-Cell Lymphoma in Pregnancy

Abstract: Primary mediastinal B-cell lymphoma (PMBCL) is a subtype of non-Hodgkin’s lymphoma, which occurs rarely in pregnancy. We present a case of a pregnant 22-year-old female who presented with syncope and dyspnea. Computed tomography (CT) chest showed an anterior mediastinal mass, and its biopsy showed PMBCL. Since she was in her second trimester, we decided to treat her with rituximab-cyclophosphamide, doxorubicin, vincristine, prednisone (R-CHOP). Our case emphasizes the safety of chemotherapy in the second and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Follow-up positron emission tomography (PET) scan noted increased size in the mediastinal mass. She was treated with rituxan, ifofasmide, carboplatin, and etopo-side for 3 weeks followed by a stem cell transplantation [16]. Similar to our case, Shulman reported chemotherapy initiated following delivery after diagnosis made during pregnancy.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Follow-up positron emission tomography (PET) scan noted increased size in the mediastinal mass. She was treated with rituxan, ifofasmide, carboplatin, and etopo-side for 3 weeks followed by a stem cell transplantation [16]. Similar to our case, Shulman reported chemotherapy initiated following delivery after diagnosis made during pregnancy.…”
Section: Discussionsupporting
confidence: 65%
“…Perez and Khalid demonstrated the safety of chemotherapy initiation for PMBCL diagnosed in the late first and second trimester [15,16]. In a Russian study, Mangasarova et al reported 8 cases of PMBCL in pregnancy that underwent chemotherapy during second and third trimesters.…”
Section: Discussionmentioning
confidence: 99%
“…A PubMed search for English-language articles describing pregnant women with PMBL treated with chemotherapy revealed four cases, including ours (Table) (12-14). In many of these cases, patients received chemotherapy during the second trimester, presumably because they were symptomatic and could not remain untreated until delivery.…”
Section: Discussionmentioning
confidence: 99%
“…According to the European League against Rheumatism (EULAR) task force, due to insufficient documentation concerning fetal safety, rituximab should be discontinued before a planned pregnancy [ 121 ]. However, so far, there have been nine case reports of patients treated with rituximab during both the first and the second trimester of pregnancy, achieving life birth in all cases [ 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 ]. Six patients were affected by hematological neoplasms, and the remaining had idiopathic thrombocytopenic purpura, vasculitis, and Goodpasture syndrome [ 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 ].…”
Section: The Current Role Of Immunosuppressant Drugs In Antiphosphmentioning
confidence: 99%